Plasma-surface interaction of electric arc discharge between composite Cu-Cr electrodes - Murmantsev, A.; Veklich, A.; Boretskij, V.; Bartlová, M.; Dostál, L.; Píška, J.; Šimek, D.; Gajdos, A.; Tolochyn, A. (Вопросы атомной науки и техники, 2020)
In this work the plasma of electric arc discharges between Cu-Cr composite electrodes, which material were pressured and sintered at different temperatures 750 or 1050°C, are investigated by Optical Emission Spectroscopy (OES). The Scanning Electron Microscopy (SEM) with Energy-Dispersive X-ray Spectroscopy (EDXS) are used to study the working surface of electrodes, modified by thermal effect of breaking electrical arc in the air atmosphere. The erosion intensity of electrodes’ material due to plasma-surface interaction is estimated in indirect way by determination of metal vapours content in the discharge gap in an assumption of local thermodynamic equilibrium (LTE). The plasma composition is calculated in this case on the base of experimentally determined plasma parameters: temperature and electron density. Методами оптичної емісійної спектроскопії досліджується плазма електродугових розрядів між композитними Cu-Cr-електродами, матеріал яких y процесі виготовлення піддавався пресуванню та спіканню при різних температурах: 750 або 1050°C. Для дослідження робочої поверхні електродів, які зазнали впливу термічної дії розривної електричної дуги в атмосфері повітря, використовується скануюча електронна мікроскопія (СЕМ), доповнена енергодисперсійною рентгенівською спектроскопією (ЕДРС). Інтенсивність ерозії матеріалу електродів внаслідок взаємодії плазма-поверхня оцінювалась у непрямий спосіб шляхом визначення вмісту парів металів у розрядному проміжку в припущенні локальної термодинамічної рівноваги (ЛТР). Склад плазми в даному випадку розрахований з експериментально отриманих параметрів плазми: температури та електронної концентрації. Методами оптической эмиссионной спектроскопии (ОЭС) исследуется плазма электродуговых разрядов между композитными Cu-Cr- электродами, материал которых в процессе изготовления подвергался прессованию и спеканию при разных температурах: 750 или 1050°C. Для изучения рабочей поверхности электродов, подвергающейся термическому воздействию разрывной электрической дуги в атмосфере воздуха, использована сканирующая электронная микроскопия (СЭМ), дополненная энергодисперсионной рентгеновской спектроскопией (ЭДРС). Интенсивность эрозии материала электродов вследствие взаимодействия плазма-поверхность оценивалась косвенным методом путем определения содержания паров металлов в разрядном промежутке в предположении локального термодинамического равновесия (ЛТР). Состав плазмы в этом случае рассчитан из экспериментально полученных параметров: температуры и электронной концентрации.